How proteins work - Mike Williamson (Garland Science, 2012)
How Proteins Work is an up-to-date and authoritative account of protein function in living systems, explained within the governing parameters of physics, chemistry, and evolution. This text will enable advanced undergraduate students in biochemistry and biophysics to understand the relationships among protein function, structure, and dynamics. It will also serve as a valuable resource for graduate students and researchers looking for a reference on the fundamentals underlying protein function. By providing an integrated view of proteins at both a cellular and systemic level, this textbook shows how evolution drives proteins to adopt domain structures that combine to achieve biological outcomes. The association of proteins into dimers, molecular machines, and multi-enzymatic complexes enables them to achieve catalytic and functional efficiency.